Simple nucleotide polymorphisms in the NRAMP1 / SLC11A1 gene to the risk of susceptibility to tuberculosis (Research, Society and Development, 2020)
Introduction: Tuberculosis is an infectious disease that has Mycobacterium tuberculosis (M. tuberculosis) as its main etiological agent, which is configured as a worldwide public health problem. Errors in the individual's immune response to the pathogen can trigger susceptibility to the infectious agent, thus, studies with SNPs in the NRAMP1 / SLC11A1 gene, have been widely carried out in investigations of susceptibility to infectious diseases, especially tuberculosis. Objective: The objective was to relate the simple nucleotide polymorphisms in the 5´Promotor, D543N, INT4 and 3´UTR variants of the NRAMP1 / SLC11A1 gene in the individual's susceptibility to M. tuberculosis through a meta-analysis. Methodology: This work was carried out following the methodological guidelines of a Systematic Review according to the PRISMA protocol, from which searches were carried out on the main Medline electronic databases via Pubmed, Science Direct and Lilacs. The studies were selected according to the eligibility criteria, with a total of 39 scientific articles chosen for data collection, without language or year restriction. Results and Discussion: The results of this study showed a possible association between the SNPs of the NRAMP1 / SLC11A1 gene with the risk of susceptibility to tuberculosis. The subgroup analysis suggested that of the 5 ethnicities and / or continents analyzed (Africa, South America, North America, Caucasian and Asians), only Caucasians did not obtain statistically significant results of any variant at a higher risk of susceptibility to tuberculosis. Conclusion: The present study showed a possible association between polymorphisms in the SNPs variant 5´Promotor, INT4, D543N and 3´UTR of the NRAMP1 / SLC11A1 gene with the risk of susceptibility to tuberculosis.